Swimbladder nematodes (Anguillicola spp.) and gill monogeneans (Pseudodactylogyrus spp.) parasitic on the European eel (Anguilla anguilla) - Køie, Marianne (ICES Journal of Marine Science, 1991)
In the past decade the large, blood-sucking swimbladder nematodes Anguillicola crassus and A. nouaezelandiae and the gill monogeneans Pseudodactylogyrus anguillae and P. bini have been introduced into Europe as a result of the uncontrolled intercontinental transfer of live eels. In Europe they have infected the European eel, Anguilla anguilla , which is more susceptible to these parasites than their original hosts. Under favourable natural conditions these potentially pathogenic helminths apparently do not cause the death of the new host. As the cultivation of eels is based on wild elvers, the parasites have entered eel farms where they have caused great economic losses.